Heterologous assisted reproductive techniques: the right to know the origin. Legislation versus subjectivity? - González, Ana Cecilia (Acta Bioethica, 2016)
Assisted reproduction techniques, in particular of heterologous type, open a variety of issues in the intersection of science, rights and subjectivity. In this paper we focus on the relation between the recently approved Argentinian legislation and the responses given by users of heterologous techniques -in this case, oocyte donation- with regard to the right to know the genetic origin. We analyse the dilemma between the law, which promotes the communication of the genetic origin to the subject born by such techniques, and the subjective factors that gravitate in the decision either to disclose the information, or keep it as a secret. Consequently, we argue that the disclosure of the genetic origin is an ethical decision, which requires the assumption of subjective responsibility. To deal with such a complex issue, we cross the data obtained in two empirical studies with theoretical contributions from legal studies, narrative bioethics, anthropology and psychoanalysis.